The Effectiveness of visual -graphic presentation on the oral health knowledge, attitude, and practices of 10-11 years old school children in Gatid Elementary School in Santa Cruz, Laguna - Cruz, Angela Roan T. (Department of Community Dentistry, University of the Philippines Manila, 2019)
INTRODUCTION: Dental caries remains to be the leading oral health disease in the Philippines (WHO, 2012) despite it being a preventable disease. Seventy-five percent of children as young as twelve years old in the Philippines have dental caries (NMEDS, 2011). A total of 87.4% Filipinos experience dental caries. Studies have shown that dental caries can be effectively reduced by tooth brushing (NIH, 2016). Hence, knowing about proper oral health care is important in reducing the high number of Filipinos suffering from dental caries. The study aimed to determine the effectiveness of visual graphic presentation as an oral health education material on the oral health knowledge, attitude and practices of 10-11 years old schoolchildren in Gatid Elementary School in Sta. Cruz, Laguna.